N-ACETYLCYSTEINEAS PARMACOLOGICAL TREATMENT IN TRICHOTILLOMANIA - Dewi, Wahyu; Ratep, Nyoman; Westa, Wayan (E-Jurnal Medika Udayana, 2013)
Trichotillomania is a compulsive disorder that characterized with repetitive hair pulling habit and results a noticeable lost off scalp, eyebrow, eyelash, armpit and pubic hair. This habit is previously started by increasing tension immediately beforehand and followed by gratification or relief afterward. Until now, all pharmacotherapies in treating patient with trichotillomania such as Selective Serotonin Reuptake inhibitor (SSRI) and Clomiperamine, and Tricycle Antidepressant (TCA) have not got approval from Food and Drug Association due to their lack effectiveness in treating compulsive habit of this disorder. In randomized control study with N-Acetylcysteine (NAC) with daily 1200-1400 mg dose that have been given for 9 weeks shows effectiveness in reducing hair pulling habit significantly in 56% patient Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: N-Acetylcysteine, trichotillomania, pharmacotherapy